Leveraging AI to optimize vaccines supply chain and logistics in Africa: opportunities and challenges - Musa, Sulaiman Muhammad; Haruna, Usman Abubakar; Aliyu, Lukman Jibril; Zubairu, Mubarak; Lucero-Prisno, Don Eliseo (Frontiers in Pharmacology, 2025)
Examining the current situation of the vaccine supply chain in Africa, the article highlights the importance of AI technologies while outlining the prospects and problems in vaccine supply chain management in Africa. Despite the significance of vaccinations, many African children are unable to receive them due to logistical challenges and a lack of infrastructure. AI has the potential to increase productivity by streamlining logistics and inventory management, but it is hampered by issues with data privacy and technology infrastructure. This perspectiveoffers ways for utilizing AI to enhance vaccine supply chains in Africa, citing successful experiences in Nigeria, Malawi, Rwanda, and Ghana as examples of AI’s advantages. In order to improve healthcare outcomes and immunization coverage in Africa, cooperation among stakeholders is stressed.